Psychometric Quality Analysis of Grade 5 Elementary School Mathematics Test Instruments: A Review Based on Validity, Reliability, and Difficulty Level Distribution Parameters - Yunni Arnidha; Novalia Novalia; Undang Rosidin; Rabiyatul Adawiyah Siregar (Jurnal Evaluasi dan Pembelajaran, 2026)
This study aimed to analyze the psychometric quality of Grade 5 elementary school mathematics test instruments based on validity, reliability, and difficulty level distribution parameters. A quantitative descriptive approach was employed, with 15 multiple-choice items administered to 49 students as the unit of analysis. Data were collected through documentation of test scripts, answer keys, and student answer sheets. Analysis was conducted using Classical Test Theory, comprising item validity through item-total correlation, reliability using Cronbach's Alpha coefficient, and difficulty level analysis based on the proportion of correct answers. Results indicated that 9 items (60%) met validity criteria, while 6 items (40%) did not. The instrument obtained a Cronbach's Alpha value of 0.753, classifying it as reliable. Difficulty level distribution showed 8 items (53.33%) in the moderate category and 7 items (46.67%) in the easy category, with no items classified as difficult. The mathematics test instrument analyzed demonstrated adequate psychometric quality; however, it still requires revision of invalid items and development of items with more varied difficulty levels to ensure more accurate and comprehensive measurement of student ability.